Investigation of the relationship between prolonged ventilation and the Glasgow Prognostic Score after elective isolated coronary bypass surgeries in advanced-age patients - Güvenç, Orhan; Engin, Mesut; Kan, Irem Iris; Yavuz, Senol (The European Research Journal, 2023)
Objectives: Coronary artery bypass graft (CABG) surgeries are the most beneficial treatment method for atherosclerotic heart disease. Prolonged ventilation is a significant condition that poses risks such as infection, renal failure, prolongs hospital stays, and increases treatment costs. In this current study, we aimed to reveal the relationship between prolonged mechanical ventilation and Glasgow Prognostic Score (GPS), in patients aged 65 years and older who underwent isolated CABG. Methods: Patients aged 65 years and over who underwent elective isolated coronary bypass surgery with cardiopulmonary bypass in our clinic, between June 2017 and June 2022, were included in the study retrospectively. The patients who were extubated within eight hours of the surgeries were determined as Group 1, whereas those who were extubated after 8 hours were determined as Group 2. Results: Prolonged ventilation occurred in 101 (20.7%) patients (Group 2). The median age of the 385 patients included in Group 1 and 101 patients in Group 2 was 68 (66 to 91) and 71 (66 to 88) years, respectively (p = 0.216). The two groups were similar in regards to gender, hypertension, smoking, diabetes mellitus, body mass index, history of cerebrovascular accident and left ventricular ejection fraction rates. In the multivariate analysis, left ventricular ejection fraction